2020
DOI: 10.1016/j.ijid.2020.05.071
|View full text |Cite
|
Sign up to set email alerts
|

Could the D614G substitution in the SARS-CoV-2 spike (S) protein be associated with higher COVID-19 mortality?

Abstract: The increasing number of deaths due to the COVID-19 pandemic has raised serious global concerns. Increased testing capacity and ample intensive care availability could explain lower mortality in some countries compared to others. Nevertheless, it is also plausible that the SARS-CoV-2 mutations giving rise to different phylogenetic clades are responsible for the apparent death rate disparities around the world. Current research literature linking the genetic make-up of SARS-CoV-2 with fatalities is lacking. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
132
2
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(147 citation statements)
references
References 6 publications
5
132
2
3
Order By: Relevance
“…As previous reported, S68F and P71L nonsynonymous mutation in E-protein of SARS CoV-2 were the most common mutation in in E-protein [22]; Q57H, G251V and G196V non-synonymous mutation in ORF3a of SARS-CoV-2 would link in the virulence, infectivity, ion channel activity and viral release [23]; deletion of ORF8 increased the interferon production and reduced in inflammatory cytokines level [24][25][26]. Most recently, researchers found that D614G non-synonymous mutation located in spike protein would increases infectivity [27][28][29][30].…”
Section: Sars-cov-2 Snvs and Protein Functionsmentioning
confidence: 99%
“…As previous reported, S68F and P71L nonsynonymous mutation in E-protein of SARS CoV-2 were the most common mutation in in E-protein [22]; Q57H, G251V and G196V non-synonymous mutation in ORF3a of SARS-CoV-2 would link in the virulence, infectivity, ion channel activity and viral release [23]; deletion of ORF8 increased the interferon production and reduced in inflammatory cytokines level [24][25][26]. Most recently, researchers found that D614G non-synonymous mutation located in spike protein would increases infectivity [27][28][29][30].…”
Section: Sars-cov-2 Snvs and Protein Functionsmentioning
confidence: 99%
“…SARS-CoV-2 S variants have been found to be circulating in the human population and it is likely that others are yet to emerge, some of which may be less sensitive to neutralization by the therapeutic monoclonal antibodies currently under development. The recently identified SARS-CoV-2 variant encoding the D614G S protein has been found to be spreading with increased frequency in the human population (Daniloski et al, 2020;Eaaswarkhanth et al, 2020;Korber et al, 2020;Zhang et al, 2020). The D614G S protein was found to be more resistant to shedding from the virion and to adopt a conformation that favors ACE2-binding and is in a more fusioncompetent state (Yurkovetskiy et al, 2020;Zhang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…CoV-2 containing a D614G point mutation in the S protein has been found to be circulating in the human population with increasing prevalence (Daniloski et al, 2020;Eaaswarkhanth et al, 2020;Korber et al, 2020;Zhang et al, 2020). The D614G mutation was found to decrease shedding of the spike protein from the virus and to assume a fusion-ready conformation, resulting in increased infectivity and most likely contributing to its increasing prevalence.…”
Section: Ace2 Microbody Blocks Entry Of Virus With D614g Mutant Spikementioning
confidence: 99%
“…5775 mutations in the SARS-CoV-2 genome were discovered from 10022 public genome data assemblies as at May 1, 2020 [9], in which missense mutations of S protein were detected. Among these spike mutations, D614G mutation, in which Aspartic acid (D) was replaced with Glycine (G) at the AA site of 614, was a major mutation of great concern [10,11]. SARS-CoV-2 with D614G mutation may have triggered fatal infections in many European countries, such as Spain, Italy, France, etc.…”
Section: Introductionmentioning
confidence: 99%
“…SARS-CoV-2 with D614G mutation may have triggered fatal infections in many European countries, such as Spain, Italy, France, etc. [11].…”
Section: Introductionmentioning
confidence: 99%